Correlation of frequency of visits to clinical nutrition outpatient clinic with body weight and handgrip strength of head and neck cancer patients undergoing chemoradiation - Luana Lidwina Latief; Diyah Eka Andayani; Yohannessa Wulandari (Indonesian Nutrition Association, 2022)
Background : Head and neck cancer patients who get chemoradiated are at risk of malnutrition and an increase in malnutrition of up to 88% at the end of chemoradiation. Side effects of chemoradiation in the form of xerostomia, mucositis, nausea or vomiting add to the decrease in nutritional status and functional capacity. Monitoring nutritional status, one of which is carried out by assessing body weight (BW) and hand-holding strength (HGS). BW and HGS assessments are a simple and minimally invasive way for people with head and neck cancer (HNC) compared to other examination tools such as body composition measuring devices, Dual Energy X-Ray Absorptiometry (DEXA), and require high costs. It is not yet known the frequency of optimal visits of HNC patients to the nutrition poly during the moradiation period. This study aims to see a correlation between the frequency of visits by HNC patients undergoing morbidity to BW and HGS.